2017
DOI: 10.1115/1.4037802
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Structural and Contact Modeling for a Silicon Hexapod Microrobot

Abstract: This paper examines the dynamics of a type of silicon-based millimeter-scale hexapod, focusing on interaction between structural dynamics and ground contact forces. These microrobots, having a 5 mm × 2 mm footprint, are formed from silicon with integrated thin-film lead–zirconate–titanate (PZT) and high-aspect-ratio parylene-C polymer microactuation elements. The in-chip dynamics of the microrobots are measured when actuated with tethered electrical signal to characterize the resonant behavior of different par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Their combination of high force generation, fast response time, and modest power consumption has made piezoelectric actuators promising for small-scaled robotics. For example, piezoelectric actuation has been used in miniature walking robots [2][3][4][5] and in anthropomorphic robotic hands [6]. However, when it becomes necessary to generate large displacement amplitudes, piezoelectric actuators are rarely ideal due to low intrinsic strain.…”
Section: Introductionmentioning
confidence: 99%
“…Their combination of high force generation, fast response time, and modest power consumption has made piezoelectric actuators promising for small-scaled robotics. For example, piezoelectric actuation has been used in miniature walking robots [2][3][4][5] and in anthropomorphic robotic hands [6]. However, when it becomes necessary to generate large displacement amplitudes, piezoelectric actuators are rarely ideal due to low intrinsic strain.…”
Section: Introductionmentioning
confidence: 99%
“…The use of micro-robots offers many advantages including minimal disturbance to users, small power requirements, portability, disposability, and ability to work in large teams and exploit swarm intelligence. Thus, micro-robotics is a very relevant and ongoing research topic that has received much attention in recent years [1][2][3][4][5][6][7][8]. Among many different types of micro-robots [1,2], MEMS-based terrestrial micro-robots are of special interest in this paper (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The realization of MEMS micro-robots or more specifically micro-robotic appendages with thin-film PZT as actuators (Fig. 1b) were of special interest in the authors' past work [7,8]. Thin-film piezoelectric materials (PZT) offer many advantages including high actuation speeds, small power consumption, high work density per unit area, and reasonable efficiency as small capacitive loads [5], relative to other MEMS transducers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, appendages based on combinations of thin-film PZT, high-aspect ratio parylene-C beams, and rigid silicon links (Fig. 1) have been demonstrated that greatly improve robot leg resilience and leverage PZT displacement into a combination of larger-angle inplane or out-of-plane motions [7,8].…”
Section: Introductionmentioning
confidence: 99%